1997
DOI: 10.1007/pl00012273
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Bronchial Stricture Due to Endobronchial Tuberculosis

Abstract: Between 1974 and 1995 we encountered 19 cases of bronchial stricture or obliteration caused by endobronchial tuberculous lesions. In 11 the involvements were located at the right bronchus (including involvements of segmental and middle lobe bronchi) and in 8 at the left bronchus. On bronchoscopic biopsy of the stenosed bronchus, 7 patients showed histopathologic findings of tuberculous bronchitis, but 12 patients showed nonspecific inflammatory granular tissue. Five patients were kept under conservative observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…Interventional bronchology and silicone airway stenting has opened up a new way to treat patients with benign airway stenosis [3,4]. Until recently, only a few studies have reported the result of bronchoscopic intervention in patients with PTTS [5][6][7][8]. However, the number of patients was ,40 in some of these.…”
mentioning
confidence: 99%
“…Interventional bronchology and silicone airway stenting has opened up a new way to treat patients with benign airway stenosis [3,4]. Until recently, only a few studies have reported the result of bronchoscopic intervention in patients with PTTS [5][6][7][8]. However, the number of patients was ,40 in some of these.…”
mentioning
confidence: 99%
“…2,3) Consequently, surgical airway plasty is commonly recommended for the treatment of tuberculous airway stenosis. [9][10][11] Eighteen patients with tuberculous airway stenosis were evaluated in this study. Six patients with tuberculous airway stenosis were treated with airway stenting alone during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe described 19 cases of bronchial stricture or obliteration due to endobronchial tuberculous lesions. Based on their findings, these authors recommended bronchoscopy and computed tomography as methods of choice for accurate diagnosis of tuberculous bronchial involvement (Watanabe Y 1997). Moreover, these modalities may aid in the assessment for surgery.…”
Section: Role Of Diagnostic Bronchoscopy In Bronchiectasismentioning
confidence: 99%